Epi—polarization with immunogold labeling for identification and localization of Mycoplasma iowae in naturally infected tissues - Shareef, Jalal M. (Sulaimani Journal for Pure and Applied Sciences, 1999)
Mycoplasma iowae is embryo lethal for turkey and chicken, but little information is available regarding the precise site of infection. This paper represents a method for obtaining a permanent record and strong illumination signals similar to those of immunofluorescence from immunogold labelled M. iowae. The purified rabbit anti M. iowae IgG and goat anti - rabbit gold labelled probe were applied for immuno - labelling the thin sectioned vagina from naturally M. iowae infected turkey hen , the sections were examined with epi-polarization microscopy. Since the site of M. iowae infeciton inside the host's body is obscure and the screening techniques for reliable monitoring are not available so far, so the present technique can be recommended for studding M. iowae in situ.